The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5152/tjg.2014.3693
|View full text |Cite
|
Sign up to set email alerts
|

The relation between liver histopathology and GGT levels in viral hepatitis: More important in hepatitis B

Abstract: Background/Aims: To investigate the relationship between gamma-glutamyl transpeptidase (GGT) levels and histopathological status determined by biopsy in patients with chronic hepatitis B and C. Materials and Methods: Patients with chronic hepatitis B and C who were referred to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 14 publications
7
20
0
Order By: Relevance
“…30 Significant relationship between liver inflammation and the level of GGT was also found in patients with CHB. 29,31 As previously reported, the AUROC of GGT was similar to that of ALT and AST, and a normal GGT excluded significant liver inflammation with 82% certainty. 12 Therefore, these data suggested that GGT was associated with liver inflammation.…”
Section: Discussionsupporting
confidence: 65%
“…30 Significant relationship between liver inflammation and the level of GGT was also found in patients with CHB. 29,31 As previously reported, the AUROC of GGT was similar to that of ALT and AST, and a normal GGT excluded significant liver inflammation with 82% certainty. 12 Therefore, these data suggested that GGT was associated with liver inflammation.…”
Section: Discussionsupporting
confidence: 65%
“…High significant increases were observed in ALT, AST, ALP and GGT at (p≤0.05) in HBV compared with control, these results are in agreement with others [22], [33][34]. ALT and GGT showed the highest increments in HBV infection, it has been stated that moderate elevation (3-20 times) of ALT level usually observed in acute hepatitis, neonatal hepatitis, chronic hepatitis, autoimmune hepatitis, drug induced hepatitis, alcoholic hepatitis [30], [33]. other study deduced that the GGT increment that reflects inflammation in, the liver is superior than ALT ,and that GGT may have a significant role in the clinical, evaluation of HBV [34].…”
Section: Discussionsupporting
confidence: 92%
“…Biomarkers are equally valuable for the estimation and assessment of hepatic disease severity due to HBV infection may alter the levels of certain liver enzymes as a result of hepatocellular damage [32]. High significant increases were observed in ALT, AST, ALP and GGT at (p≤0.05) in HBV compared with control, these results are in agreement with others [22], [33][34]. ALT and GGT showed the highest increments in HBV infection, it has been stated that moderate elevation (3-20 times) of ALT level usually observed in acute hepatitis, neonatal hepatitis, chronic hepatitis, autoimmune hepatitis, drug induced hepatitis, alcoholic hepatitis [30], [33].…”
Section: Discussionsupporting
confidence: 85%
“…GGT levels were found to be correlated with histo pathological alteration in many hepatic disorders [45] . The increase in GGT in the present study was an indicator for damaging effect of AA on rat hepatic tissue this could be based on previous reports that find an increase in GGT levels in both human and animals exposed to hepatitis inducing agents, special medication, or chemical toxicant insult [46,47] .…”
Section: Ggt and Total Antioxidant Capacitysupporting
confidence: 55%